Role expectations and role performance of Agricultural Extension Officers, - V.K.Reddy (Journal of Agricultural Extension Management, 2025)
Agricultural Extension Officer (AEO) is the front line worker for extension and key functionary in agricultural development at cutting edge level in the State of Andhra Pradesh. Originally conceived as multipurpose functionary and designated as village level worker, he was to act as a friend, philosopher and guide to the villagers. With the introduction of Training and Visit (T & V) System of extension in seventies, an attempt was made to redefine his role so as to focus exclusively more specifically on extension itself. In the light of the experience of T & V system and in the context of the importance of participatory and farming situation based extension, there were attempts to delineate the role again. An AEO was expected to diagnose farming situations and identify farmers’ problems. He should not focus only on technical message to be transferred but need to learn more about the farmers, their farming system, the ecological characteristics of the areas, particularly about the farmers’ behaviour and reasons for doing things the way they do. While the role as defined under T & V system by and large remained, changes were effected to meet specific requirements and on-going initiatives. Now the issue is, as to what extent the new roles and responsibilities are performed